Turning the Tap: Conformational Control of Quantum Interference to Modulate Single‐Molecule Conductance. (31st October 2019) - Jiang, Feng; Trupp, Douglas I.; Algethami, Norah; Zheng, Haining; He, Wenxiang; Alqorashi, Afaf; Zhu, Chenxu; Tang, Chun; Li, Ruihao; Liu, Junyang; Sadeghi, Hatef; Shi, Jia; et al.
Abstract: Together with the more intuitive and commonly recognized conductance mechanisms of charge‐hopping and tunneling, quantum‐interference (QI) phenomena have been identified as important factors affecting charge transport through molecules. Consequently, establishing simple and flexible molecular‐design strategies to understand, control, and exploit QI in molecular junctions poses an exciting challenge. Here we demonstrate that destructive quantum interference (DQI) in meta ‐substituted phenylene ethylene‐type oligomers ( m ‐OPE) can be tuned by changing the position and conformation of methoxy (OMe) substituents at the central phenylene ring. These substituents play the role of molecular‐scale taps, which can be switched on or off to control the current flow through a molecule. Our experimental results conclusively verify recently postulated magic‐ratio and orbital‐product rules, and highlight a novel chemical design strategy for tuning and gating DQI features to create single‐molecule devices with desirable electronic functions. Abstract : Aufgedrehter Hahn : Die Veränderung der Konformation und Position einer Methoxygruppe an einer molekularen Kontaktstelle führt zu einem Wasserhahn‐artigen Verhalten, mit dem sich die elektrische Leitfähigkeit des Systems präzise an‐ und ausschalten lässt. Der Ansatz liefert einen simplen Weg, um Ladungstransport bei Raumtemperatur auf der Einzelmolekülskala zu kontrollieren.